Method for measurement and reporting of local vibration data of ship structures and equipment (BSI, 1985)
Ships, Cargo ships, Water transport engineering, Vibration, Vibration measurement, Superstructures (ships), Water transport engineering components, Ships bodies, Decks, Ships bulkheads, Ships masts, Measurement, Position, Testing conditions, Test equipment, Inland waterway transport, Tugboats